2020
DOI: 10.1021/acs.macromol.0c01976
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Durable Poly(phenylene-co-arylene ether) Multiblock Copolymer-Based Anion Exchange Membranes with Different Hydrophobic Moieties for Application in Fuel Cells

Abstract: Quaternized multiblock poly(phenylene-co-arylene ether)s (QPPs) are synthesized from a pre-aminated monomer and a series of chlorine-terminated oligo(arylene-ethers) via a nickel coupling reaction. Their properties are investigated as anion exchange membranes with the goal of obtaining membranes with enhanced performance and durability for alkaline membrane fuel cell applications. Three different oligo(arylene ethers) were synthesized and introduced in the hydrophobic block of the polymer backbone to study its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…(a) Swelling ratio; (b) water uptake; (d) OH – ionic conductivity of the QPDI-a; (e) Arrhenius plot: ionic conductivity vs 1000/ T ; and (c,f) comparison of hydroxide conductivity of QPDI-a with some literature-reported AEMs at 80 °C at different IEC values and swelling ration. ,,, , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(a) Swelling ratio; (b) water uptake; (d) OH – ionic conductivity of the QPDI-a; (e) Arrhenius plot: ionic conductivity vs 1000/ T ; and (c,f) comparison of hydroxide conductivity of QPDI-a with some literature-reported AEMs at 80 °C at different IEC values and swelling ration. ,,, , …”
Section: Resultsmentioning
confidence: 99%
“…The high conductance of QPDI-a is attributable to the free volume constructed by the rigid twisted backbone of AEMs and also because the long flexible ion chain is easy to rotate and aggregate. The combination of these two factors better allows for ion conduction channels to be established. ,,, , The structural advantages of QPDI-a confer excellent properties such as high conductance and size stability and hence, it has high performance and more promising applications in AEMs.…”
Section: Resultsmentioning
confidence: 99%
“…A few solutions have been developed to enhance the alkaline stability of PAEs. Bae et al synthesized quaternized multiblock poly(phenylene-coarylene ether)s from a "pre-aminated" monomer and a series of chloro-terminated oligo(arylene ether)s. 14 These copolymers exhibited enhanced fuel cell performances and alkaline durability because of the well-defined microphase separation of the hydrophilic and the hydrophilic domains and the presence of the phenylene-based structures in the hydrophilic domains. In contrast, He et al converted the electronwithdrawing CO groups in the conventional poly(aryl ether ketone) (PEAK) backbone into the electron-donating C−NH 2 groups through the Leuckart reaction, thus alleviating the nucleophilic attack of OH − to the ether-connected phenyl−C in the elevated electron cloud density environment.…”
Section: Freeman Et Al Developed a New And Simple Methods To Determin...mentioning
confidence: 99%
“…A few solutions have been developed to enhance the alkaline stability of PAEs. Bae et al synthesized quaternized multiblock poly­(phenylene- co -arylene ether)­s from a “pre-aminated” monomer and a series of chloro-terminated oligo­(arylene ether)­s . These copolymers exhibited enhanced fuel cell performances and alkaline durability because of the well-defined microphase separation of the hydrophilic and the hydrophilic domains and the presence of the phenylene-based structures in the hydrophilic domains.…”
mentioning
confidence: 99%
“…Common commercial polymers such as poly­(phenylene oxide)­s (PPOs), poly­(aryl ether sulfone)­s (PAESs), and poly­(aryl ether ketone)­s (PAEKs) , can be employed as the polymer backbone of AEM materials. PPOs and PAESs are easily attacked by a potent nucleophile-hydroxide ion in alkaline media, resulting in the degradation of the polymer main chain, which includes aryl ether hydrolysis or quaternary carbon hydrolysis. , Many studies have shown that polymer backbones without aryl ethers can greatly prevent hydroxide ions from attack under alkaline conditions. , Yan and coworkers reported the synthesis of poly­(aryl piperidinium) without aryl ether groups, and the corresponding AEMs maintained ionic conductivity and flexibility after being immersed in 1 M KOH solution at 100 °C for a long time .…”
Section: Introductionmentioning
confidence: 99%